Efficacy of combination therapy with omeprazole, amoxicillin and clarithromycin for treatment of patients with Helicobacter pylori associated gastritis and duodenal ulcer disease - Yeşim ERALP,; Can DAVUTOĞLU,; Hülya UZUNİSMAİL,; Ergun OKTAY, (Turkish Journal of Gastroenterology, 2019)
-